Digital Skills Development and Workforce Innovation: A Systematic Review of Human Capital Management in Education - Zulbilal, Ahmad; Torrido, Aryan; Mardiyah, Mardiyah (Universitas Islam Negeri Raden Intan Lampung, 2024)
The rapid technological transformation in the 21st century has brought fundamental changes to the world of education, requiring educators to master digital skills and be adaptive to technological changes. Human Resource Management (HCM) is a relevant strategic framework to support the development of digital skills and workforce innovation in education. This study aims to explore trends, challenges, and opportunities in digital skills development through the HCM approach. Using a systematic literature review method based on the PRISMA protocol, 20 articles published between 2019–2024 were analyzed with a focus on